Baby's first toys book. (Chichester, [England] : Brimax, 2003)
"This sturdy board book teaches babies and toddlers how to identify toys. Featuring bold, bright illustrations, this fun first toys book is perfect for parents to read aloud with their child as they point to the different toys."--P. [4] of cover.
Title from cover.
On board pages.
Keywords: Toys